2010
DOI: 10.1017/s1833367200001905
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cause-related marketing (CRM) in spectator sport

Abstract: Cause-related marketing (CRM) refers to the marketing strategy an organization uses to associate itself with a good cause. Even though CRM decisions may be partly charitable, they may also serve corporate self-interest. Although this area of inquiry is growing, CRM's strategic potential as an effective management tool for connecting sport organizations (i.e., teams) with consumers has not been thoroughly examined in a sport management context. In order to provide an improved picture of spectator sport consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 53 publications
4
20
0
Order By: Relevance
“…Korean professional baseball teams have also initiated various CRM campaigns partnered with several social causes such as cheerleading, baseball, and mentoring classes for local youths and baseball day programs that provide an opportunity for the underprivileged to watch baseball games [27]. In conclusion, the CRM campaigns carried out by professional sport teams can be considered a promising means of communication that reinforces the sport teams' brand equity [11].…”
Section: Cause-related Marketing and Its Consequencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Korean professional baseball teams have also initiated various CRM campaigns partnered with several social causes such as cheerleading, baseball, and mentoring classes for local youths and baseball day programs that provide an opportunity for the underprivileged to watch baseball games [27]. In conclusion, the CRM campaigns carried out by professional sport teams can be considered a promising means of communication that reinforces the sport teams' brand equity [11].…”
Section: Cause-related Marketing and Its Consequencesmentioning
confidence: 99%
“…Extant studies have reported that CRM motive perceived by consumers affects brand attitude [10,11]. Consumers, in general, tend to interpret a firm's CRM campaign as a dichotomy of a cause-oriented or profit-oriented motive [12].…”
Section: Cause-related Marketing and Its Consequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several papers discuss the CSR related activities of sport organizations. First, Kim, Kwak and Kim (2010) consider the motives for cause-related marketing (CRM) in sports -an area that has received scant examination in the sport marketing context. The authors found justifi cation for at https://www.cambridge.org/core/terms.…”
Section: Introduction To the Special Issuementioning
confidence: 99%